2020
DOI: 10.1101/2020.06.21.162990
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ADA2 is a lysosomal DNase regulating the type-I interferon response

Abstract: Deficiency of adenosine deaminase 2 (DADA2) is a severe, congenital syndrome, which manifests with hematologic, immunologic and inflammatory pathologies. DADA2 is caused by biallelic mutations in ADA2, but the function of ADA2, and the mechanistic link between ADA2 deficiency and the severe inflammatory phenotype remains unclear. Here, 5 we show that monocyte-derived proteomes from DADA2 patients are highly enriched in interferon response proteins. Using immunohistochemistry and detailed glycan analysis we dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…LMW-ADA2 protein levels did however not increase upon proteasome inhibition ( Figure S8C ). We therefore assume that glycan trimming and retro-translocation of LMW-ADA2 generate a functional cytosolic or lysosomal protein that might be different in function of secreted HMW-ADA2, as suggested by Greiner-Tollersrud and colleagues (17).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…LMW-ADA2 protein levels did however not increase upon proteasome inhibition ( Figure S8C ). We therefore assume that glycan trimming and retro-translocation of LMW-ADA2 generate a functional cytosolic or lysosomal protein that might be different in function of secreted HMW-ADA2, as suggested by Greiner-Tollersrud and colleagues (17).…”
Section: Discussionmentioning
confidence: 90%
“…Differences in the molecular weight of a protein can be caused by posttranslational protein modifications and N-glycosylation of ADA2 has previously been confirmed (10,12,17). Therefore, we initially hypothesized that the LMW-form of ADA2 unique to cells expressing WT ADA2 corresponded to glycan-free ADA2.…”
Section: Human Monocyte-derived Macrophages Intracellularly Express A...mentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, it is likely that ADA2 plays a very insignificant role, if any at all, in the metabolism of adenosine in beta-cells. Instead, it has recently been reported that ADA2 functions as a growth factor ( 39 ) or possibly as an interferon-I response factor ( 40 ), which may explain why ADA2 overexpression instead potentiates beta-cell death in the presence of a high adenosine concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular adenosine levels were analysed using an ELISA and expressed per mg protein. Frontiers in Endocrinology frontiersin.org it has recently been reported that ADA2 functions as a growth factor (39) or possibly as an interferon-I response factor (40), which may explain why ADA2 overexpression instead potentiates beta-cell death in the presence of a high adenosine concentration. The low expression level of the ADA1 protein in EndoC-betaH1 cells is probably explained, at least in part, by miRNA-mediated suppression of ADA1 translation.…”
mentioning
confidence: 99%